Malay declarative sentence: Visualization and sentence correction - Muhamad Noor, Yusnita; Jamaludin, Zulikha (2012)
Language researchers introduced sentence parse tree visualizations to help in understanding sentence structure, especially in English. Among the applications introduced, phpSyntaxTree and RSyntaxTree give users the opportunity to visualize an English sentence through online interaction.In Malaysia, language research in sentence parse tree visualization for Malay (BM) still hasn’t attracted enough researchers to produce a prototype as has been done in English.However, several parsers for BM sentences have been introduced.The parsers will produce a parse tree as an output from the parsing process. Based on the parsers, methods can be extended to produce sentence parse tree visualizations for BM. Parsers for checking sentence structure need to be included in visualization methods.Visualization methods involved consist of 1) tokenizing, 2) checking the number of words, 3) assigning word class, 4) checking spelling or conjunctions, 5) checking and matching with formula, 6) suggestion or visualization 7) word attributes and 8) visualization from a corpus.A prototype for the methods introduced is still under the development and improvement process.However output from the development process in validating the sentence, giving corrections for incorrect sentences and creating a parse tree has had good output results.